Determination of Detonation Wave Velocity in an Explosive Gas Mixture - Polatayko, M.M. (Ukrainian Journal of Physics, 2012)
The well-known formula for the flat detonation wave velocity derived from the Hugoniót system of equations faces difficulties, if being applied to a spherical reactor. A similar formula has been obtained in the framework of the theory of explosion in reacting gas media with the use of a special model describing the transition of an explosive wave in the detonation. The derived formula is very simple, being also more suitable for studying the limiting processes of volume detonation.